Impact of Game-based learning on oral production into the English as a Foreign Language (EFL) classroom in second graders - García Macías , Viviana Lisbeth; Castillo Noriega , Martha Amelia (Arandu UTIC, 2025)
This research aims to determine whether Game-Based Learning (GBL) improves the English language proficiency of students in the realms of vocabulary, fluency, and accuracy. An experimental design was employed, featuring two groups of second-grade students within a trilingual (Spanish, English, French) school located in Machala, Ecuador. Group A engaged in English lessons delivered through Game-Based Learning methodologies, while Group B received conventional instruction. The pedagogical repertoire of Group A included games such as "Snakes and Ladders," "Twister," and "Killing Flies." Pre- and post-tests were administered to measure linguistic competence, and student surveys and teacher observations were utilized to gather additional data during the implementation. The findings suggest that Game-Based Learning is an effective approach to improving the linguistic skills of young learners. A statistically significant divergence was observed between the two cohorts. Notably, Group A exhibited a marked enhancement, particularly in fluency and vocabulary, where the students manifested an improvement rate of +6.8% and +2.7% respectively, when contrasting with the outcomes witnessed in Group B, Game-Based Learning represents a significant pedagogical approach in the teaching of the English language, warranting further academic research into its effectiveness and optimal implementation in diverse elementary educational settings.